Daya Ikat Perjanjian Jual Beli dalam Marketplace Shopee Dengan Sistem Pembayaran Cash On Delivery (COD) - Angelia Putriana (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The era of digital transformation has changed the way many businesses operate, communicate and compete. In this era, businesses need to develop relevant strategies to remain competitive. Contemporary businesses are undergoing digital transformation, the role of a viable strategy has become very important for any company. There are various important aspects to focus on when developing a digital business strategy: primarily, increasing the scope of business operations as well as implementing the latest IT solutions to make this strategy a long-term “scale-up” plan intended to maintain the company's viability, performance and contribute to the achievement of Development Goals Sustainable (SDGs). The purpose of this article is to analyze the development of efficient business strategies in the digital era. The method used in this analysis is a qualitative descriptive method. The results of this discussion show that in the era of the “new economy” and the digital transformation that accompanies it, an innovative digital business strategy based on advanced IT solutions and aligned with the SDGs is a great opportunity for companies to deviate from competitors and gain a competitive advantage.